ANALISIS PENGARUH PROMOSI, HARGA, DAN ATRIBUT PRODUK TERHADAP PERPINDAHAN MEREK (BRAND SWITCHING) KARTU SELULER - Jatmiko, Robby (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2017)
Brand Switching is the time when a customer or a group of customerchange their loyalty from one brand of product to another. Population of thisresearch is SIM Card User in Totalwin Semarang. Sixty eight are chosen assample are fixed as purposive sampling. Data are analyzed using SPSSprogram. Data are collected with questionnaires.From the research we canconclude that validity test and reliability test all questioner are fulfill therequirement. Result and theoretical implication of this research is: thisresearch supports previous researches postulating that promotion, price , andproduct attributes influences to brand switching positively. In managerialterms, this research contributes to decision makers to pay more attention tothe promotion in purpose to improve loyalty customer.